2010
DOI: 10.1016/j.foreco.2010.02.013
|View full text |Cite
|
Sign up to set email alerts
|

Detecting interspecific and geographic differentiation patterns in two interfertile oak species (Quercus petraea (Matt.) Liebl. and Q. robur L.) using small sets of microsatellite markers

Abstract: a b s t r a c tGenetic analysis was carried out in order to provide insights into differentiation among populations of two interfertile oak species, Quercus petraea and Quercus robur. Gene flow between the two species, local adaptation and speciation processes in general, may leave differential molecular signatures across the genome. Three interspecific pairs of natural populations from three ecologically different regions, one in central Europe (SW Germany) and two in the Balkan Peninsula (Greece and Bulgaria… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
63
4
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(84 citation statements)
references
References 54 publications
13
63
4
4
Order By: Relevance
“…The results obtained for the observed heterozygosity are consistent with those reported for Q. pubescens in France (Lepais et al 2006) and with those reported for other white oak species, such as sessile oak or pedunculate oak in stands from Greece, Bulgaria, and Germany (Neophytou et al 2010). …”
Section: Discussionsupporting
confidence: 90%
“…The results obtained for the observed heterozygosity are consistent with those reported for Q. pubescens in France (Lepais et al 2006) and with those reported for other white oak species, such as sessile oak or pedunculate oak in stands from Greece, Bulgaria, and Germany (Neophytou et al 2010). …”
Section: Discussionsupporting
confidence: 90%
“…Moreover, the level of genetic differentiation detected (F ST = 0.12) is markedly high as compared to that observed in oak populations closer to the core of their distribution. For comparison, using 14 microsatellite loci, Neophytou et al (2010) observed a notably lower F ST of 0.04 among three Q. robur populations located in Germany, Greece and Bulgaria, respectively, i.e. across a geographic range much larger than the one covered by the present study.…”
Section: Regional Differentiation Among Oak Populationscontrasting
confidence: 65%
“…The balance achieved by a population among these factors determines its special genetic structure (Valencia-Cuevas et al, 2014). Genetic structure can be associated with geographical region, climate conditions (Neophytou et al, 2010), hybridization (Curtu et al, 2014), breaking of primary reproductive barriers (Valencia-Cuevas et al, 2014), altitude, historical movements, evolution, phenology and seed dispersal over a large area by animals (Ohsawa et al, 2007;Zhang et al, 2013 andWang et al, 2014).…”
Section: Resultsmentioning
confidence: 99%